AKTIVITAS INHIBISI α-GLUKOSIDASE DARI EKSTRAK AIR DAN ETANOL DAUN SIMPUR AIR (Dillenia suffruticosa (Griff.) Martelli) - Sitaresmi Yuningtyas; Anna P. Roswiem; Erfina (Jurnal Farmamedika (Pharmamedika Journal), 2018)
Diabetes mellitus is a disorder of carbohydrate metabolism which characterized by hyperglycemia conditions. One of the mechanism from oral hypoglycemic drug is inhibition of α-glucosidase activity. Dillenia suffruticosa (Griff.) Martelli, known as "simpur air" has been used to treat diabetes mellitus. This study aims to determine the inhibition activity of α-glucosidase enzyme from water and ethanol extract simpur air leaves. Simpur air leaves extracted with water and ethanol 70% using maceration method. Parameter evaluated in this research were phytocemical screening and alpha glucosidase inhibiting (AGI) activity. The results showed that the active compounds in water and ethanol extracts were flavonoids, saponins and tannins. AGI activity in water extract from simpur air leaves at concentrations of 1%, 1.5% and 2% were 1.49%, 2.76% and 3.91%, respectively. AGI activity in ethanol extract from simpur air leaves at concentrations of 1%, 1.5% and 2% were 92.10%, 98.10% and 118.30%, respectively. While the AGI activity from glucobay were 99.50%. The optimum of AGI activity was in 1.5% ethanol extract. This AGI acivity which was not significantly different (α<0.05) from the 1% glucobay.